PENGARUH KOMBINASI SENAM LANSIA DENGAN BERDIRI JINJIT TERHADAP PENURUNAN NYERI SENDI PADA LANSIA - Marwiati Marwiati; Abdullah Azam Mustajab; Siti Khoiriyah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) UNSIQ, 2023)
The elderly is an individual who experiences various deteriorations of organ function so that it is susceptible to diseases and infections. Joint pain is a chronic complaint of the elderly, the main pain occurs when waking up in the morning which makes the elderly even more unproductive. The experimental quasy study was used in this study with post test only control design approach for the elderly given routine elderly gymnastics by combining with tiptoe standing. The results of the study found that the elderly experienced a decrease in joint pain, the joint muscles of the legs became more flexible and because the elderly gymnastics was carried out together, the elderly became happier so that they felt more comfortable. The combination of physical therapy of elderly gymnastics, gathering together with peers and music rhythms is a psychosocial impact that can reduce pain in addition to walking in place and tiptoe standing can train muscle strength and flexibility.